Histone acetylation and expression of mono-aminergic transmitters synthetases involved in CUS-induced depressive rats. (March 2014) - Liu, Dan; Qiu, Hong-Mei; Fei, Hui-Zhi; Hu, Xiao-Ya; Xia, Hai-Jian; Wang, Li-Jia; Qin, Li-Juan; Jiang, Xin-Hui; Zhou, Qi-Xin
Histone acetylation has been linked to depression, the etiology of which involves many factors such as genetics, environments, and epigenetics. The aim of the present study was to investigate whether it was associated with epigenetic histone modification and gene expression of enzymes responsible for the biosynthesis of norepinephrine and serotonin in rat depression model induced by chronic unpredictable stress (CUS). Eight-week-old male Sprague-Dawley rats were exposed to CUS over 28 days. It was shown that the CUS-induced rats displayed remarked anxiety- and depression-like behavior with weakened locomotor activity in open field test and prolonged immobility in forced swimming test. Western blot revealed that CUS led to significant decrease in acetylation of H3 at Lysine 9 (K9) and H4 at Lysine 12 (K12) with obviously increasing histone deacetylases 5 (HDAC5) expression in hippocampus of CUS-induced rats. Meanwhile, there was an obviously decreased expression of tyrosine hydroxylase (TH) and tryptophan hydroxylase (TPH) both at protein and mRNA levels. Administration of sodium valproate (VPA), a histone deacetylase 5 (HDAC5) inhibitor, not only significantly relieved the anxiety- and depression-like behaviors of CUS-induced rats but also clearly blunted decrease of H3(K9) and H4(K12) acetylation and expression of TH and TPH, and prevented increase of HDAC5 expression. The results indicate that there exists possible interrelation between TH and TPH gene expression and epigenetic histone acetylation in CUS-induced depressive rats, which at least partly contributes to the etiology of depression.